Episodic antiretroviral therapy increases HIV transmission risk compared to continuous therapy: results of a randomized controlled trial - Burman, William (2008)
OBJECTIVE: To compare HIV transmission risk among patients randomized to episodic vs. continuous antiretroviral therapy. DESIGN: This was a substudy of the Strategies of Management of Antiretroviral Therapy (SMART) study, in which patients were randomized to continuous vs. CD4+ guided episodic antiretroviral therapy. Participants were surveyed about sexual activity and needle-sharing and had laboratory testing for gonorrhea, chlamydia, and syphilis. RESULTS: 883 patients enrolled; the mean age was 45 years, 25% were women, and 78% were on antiretroviral therapy. At baseline, 136 participants (15.4%) had high-risk behavior (vaginal or anal sex without a condom, needle-sharing, or incident bacterial sexually-transmitted infection). Following randomization, the proportion of participants reporting high-risk behavior was stable and did not differ by randomized arm (p = 0.39). Among participants off therapy at baseline, high-risk behavior was less common 4 months after randomization among those who were randomized to start antiretroviral therapy (p = 0.03). HIV transmission risk (high-risk behavior while HIV-RNA level > 1500 copies/ml) with partners perceived to be HIV-uninfected was higher in the episodic therapy arm (p = 0.02). CONCLUSIONS: Patients on episodic antiretroviral therapy did not decrease high-risk behavior, and because HIV-RNA levels were higher, this strategy may result in increased HIV transmission.